Education of the countryside, waters and forests: the peasantry in the poetic song “Xote Ecológico” - Ronaldo dos Santos Leonel; Everton Bedin (Revista Brasileira de Educação do Campo)
This essay analyses the intersection between Rural Education, the representation of the peasantry in the song "Xote Ecologic" by Luiz Gonzaga and Aguinaldo Batista, and the socio-environmental impacts of the Belo Monte Dam in the Xingu. It explores Rural Education as a means of rural inclusion and development and investigates how the song reflects the relationship between the peasantry and environmental degradation. The methodology adopted in this study is based on contextualized critical analysis, aiming to understand the song in its broader socio-environmental context. This approach integrates two fundamental perspectives: musical hermeneutics and bibliographic review. The study highlights the critical representation of the peasantry in the song, revealing challenges and struggles for environmental preservation and contributes to the understanding of the complex interactions between society, environment, and peasant culture, and emphasizes the importance of Rural Education for equitable and sustainable development. Therefore, from this analysis, it becomes evident that the song "Xote Ecológico" transcends its artistic form and becomes a valuable document for understanding the complex interactions between society, environment, and culture, by reminding us of the importance of considering the environmental implications of modern agricultural practices and unbridled urban expansion.